Voice disorders - Sapienza, Christine M.; Hoffman, Bari (San Diego : Plural Publishing, 2022)
'With Voice Disorders, Fourth Edition, authors Christine Sapienza, PhD and Bari Hoffman, PhD have created a comprehensive package for learning. The authors uniquely blend voice science with voice treatments ranging from traditional interventions to recent advances in cellular therapies, muscle strength training, and treatments for special populations. The text has been extensively updated with clinical evidence-based information and comes with a robust online companion website including a study workbook, videos, audio files, and case studies'--
Respiratory Anatomy and Physiology -- Laryngeal Anatomy and Physiology -- Vocal Health -- Evaluation -- Vocal Pathology -- Neurologically Based Voice Disorders -- Vocal RehabilitationBiofeedback Techniques -- Management: Phonosurgery -- Team Management of Head and Neck Cancer -- Vocal Performance -- Drug Types and Effects on Voice -- Immune System Response to Diseases and Its Impact on -- Laryngeal Reflexes
Includes bibliographical references and index.
Keywords: Voice Disorders; Voice -- physiology; Larynx -- physiopathology; Electronic books